Chile and Japan During the Thousand Allende S Days, 1970-1973: The Side Road [Chile y Japón Durante Los Mil Días de Allende, 1970-1973: El Camino Lateral] - Ross-Orellana, C (Universidad de Talca, 2014)
The Cold War (1947-1991) was characterized by the well-known East-West ideological bipolarity, which had global reach and covering all aspects of public and private life. Japan and Latin America came under the hegemony of the United States and, consequently, their relations were formally subject to the rigidities of this historical context. However, tensions between Washington and Tokyo and international pragmatism of the Allende government (1970-1973), were the keys to the relationship between Santiago and Tokyo in a model characterized by heterodoxy, in a scheme that deviated from the general rules of the Cold War and we have called "side" relationships.